Education management in the sirah of the Prophet Muhammad SAW and its implications in the modern era - Isnawan, Faris; Khuriyah, Khuriyah; Supriyanto, Supriyanto (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This article aims to discuss the superior intellectual, emotional, and spiritual intelligence of the Prophet Muhammad Rasulullah SAW. Literature research is used by various hadiths to explain the intelligence of Rasulullah SAW, such as his ability to remember or memorize revealed revelations and his kindness and respect for non-Muslims at that time, which made him a figure admired by the world—not only Muslims but also non-Muslims. . The Prophet rose to the position of being the most perfect intelligence because he possessed the highest intelligence, namely his spiritual intelligence, which he demonstrated through his piety to Allah, submission to Him, and the ability to see things deeply and essential. According to history, the Prophet Muhammad SAW prepared Allah SWT to become a Messenger not only for the apathetic Arab people of his time but also for the whole world until the end of time. All of the Prophet's intelligences are equated with intelligence in psychological research.